Enhanced Oral Bioavailability of the Pharmacologically Active Lignin Magnolol via Zr-Based Metal Organic Framework Impregnation - Joshua H. Santos; Mark Tristan J. Quimque; Allan Patrick G. Macabeo; Mary Jho-Anne T. Corpuz; Yun-Ming Wang; Tsai-Te Lu; Chia-Her Lin; Oliver B. Villaflores (MDPI AG, 2020)
Bioavailability plays an important role in drug activity in the human body, as certain drug amounts should be present to elicit activity. However, low bioavailability of drugs leads to negligible use for human benefit. In this study, the diversely active neolignan, magnolol, was impregnated onto a Zr-based organometallic framework [Uio-66(Zr)] to increase its low bioavailability (4-5%) and to test its potential acute oral toxicity. Synthesis of Uio-66(Zr) was done through the solvothermal method while simple impregnation at different time points was used to incorporate magnolol. The loading capacity of Uio-66(Zr) at 36 h was found to be significantly higher at 72.16 ± 2.15% magnolol than in other incubation time. Based on the OECD 425 (limit test), toxicity was not observed at 2000 mg kg−1 dose of mag@Uio-66(Zr) in female Sprague Dawley rats. The area under the curve (AUC) at 0-720 min of mag@Uio-66(Zr) was significantly higher than the AUC of free magnolol. Moreover, relative bioavailability increased almost two-folds using Uio-66(Zr). Unconjugated magnolol was found in the liver, kidney, and brain of rats in all treatment groups. Collectively, Uio-66(Zr) provided a higher magnolol bioavailability when used as drug carrier. Thus, utilization of Uio-66(Zr) as drug carrier is of importance for maximal use for poorly soluble and lowly bioavailable drugs.